The course of rheumatoid arthritis in able-bodied persons - T M Chernykh; Inna Alekseyevna Baryshnikova (Научно-практическая ревматология)
Objective: to study the course of rheumatoid arthritis (RA) in able-bodied patients according to the data of a hospital registry. Subjects and methods. A group of 423 (65.9%) able-bodied patients (18-60-year-old men and 18-55-year-old women) was singled out in the reg istry of inpatients (n=642). The study was performed using 70 parameters including sociodemographic, clinical laboratory, and functional signs. Results. In the study group, the able-bodied patients with RA aged less than 30 years were 5.2%; those aged 31 to 40, 41 to 50, and over 50 years were 14.9, 46.6, and 33.3%, respectively. There was a female preponderance (79.0%) in the all age groups. The disease duration of less than 1 year was observed in 7.6 cases; that of 1 to 2, 2 to 10, and more than 10 years was in 14.2, 44.4, and 33.8% of cases. The age peak of onset was noted at 31-50 (44±5.0) years of age. Among the examinees, 55.1% of the patients were unemployed; 54.5% were disabled, including 34.5% who had Groups I and II disability. Seropositive RA was recorded in 93.6% of cases; second- and third-degree activity of the pathological process in 79.7%; erosive arthritis (Stage II–IV RA) in 83.4%; Functional Class III or IV in 85.6%. Conclusion. The findings suggest that RA is an urgent problem for able-bodied persons, which determines the need for improving its early diagnosis at the primary health care level with the further effective monitoring of the course of the disease and the efficiency of therapy.